The Effect of Modifications of Challenge Board Games and Traditional Engklek Games on The Movement of Locomotors in Mild Children - Ristin Paramesthi; Soegiyanto Soegiyanto; Harry Pramono (JUARA : Jurnal Olahraga, 2022)
The background of the problem is the low locomotor movement ability in mild mentally disabled children during physical education learning. The aims of this study were 1) to analyze the effect of modifying the challenge board game on the locomotor abilities of mild mentally disabled children in SLB. 2) Analyzing the influence of traditional games on the locomotor movement abilities of mild mentally disabled children in SLB. 3) Analyzing the comparison of modified challenge board games and traditional engklek games on the locomotor abilities of mild mentally disabled children in SLB. This study uses an experimental method with a one-group pretest-posttest design, and the data analysis technique uses a paired sample T-Test at a significant level (α: 0.05). The population in this study were all children with mental retardation at the junior high school level at SLB Muhammadiyah Kertososno, SLB Hardika Bakti Peterongan Jombang, and SLB Tunas Harapan 2 Peterongan Jombang. The sample in this study was purposive sampling, namely 21 mild mentally disabled children. The results based on SPSS calculations, on the pair of the effect of modified challenge board game and the results on the team of the impact of the traditional engklek game on the locomotor ability of mild mentally disabled children in SLB, obtained the value of Sig. (2-tailed) of 0.000. H0 is accepted if the value of Sig: is 0.05, and H0 is rejected if Sig <. This means that if the Sig (0.000) value <0.05, then H0 is rejected. The results of the t-test using the average post-test challenge board game where the group using the challenge board game is 72.0129 compared to the group using the traditional engklek game, which is 66.9614. This shows that the challenge board game improves locomotor movement skills in mild mentally disabled children compared to the traditional engklek game exercise.